2011
DOI: 10.1016/j.jcin.2011.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Percutaneous Coronary Intervention for Chronic Total Occlusions

Abstract: Successful CTO PCI is associated with reduced long-term cardiac mortality and need for coronary artery bypass graft surgery. Treatment of CTO with DES rather than BMS is associated with a significant reduction in target vessel revascularization with similar rates of stent thrombosis. Paclitaxel-eluting stents and sirolimus-eluting stents had similar long-term safety and efficacy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
181
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 284 publications
(201 citation statements)
references
References 28 publications
14
181
2
4
Order By: Relevance
“…I am not truly surprised for the benefit in mortality, because it confirms somehow the data reported in previous observational or post-hoc studies [1][2][3][4][5][6]. I find also clinically unacceptable stating that a treatment is non-inferior to another one, based on a composite endpoint, when its different components move clearly in different directions for each therapeutic option.…”
supporting
confidence: 75%
“…I am not truly surprised for the benefit in mortality, because it confirms somehow the data reported in previous observational or post-hoc studies [1][2][3][4][5][6]. I find also clinically unacceptable stating that a treatment is non-inferior to another one, based on a composite endpoint, when its different components move clearly in different directions for each therapeutic option.…”
supporting
confidence: 75%
“…Several previous observational studies and meta‐analysis regarding clinical outcomes in patients with successful CTO PCI have demonstrated its beneficial effect, such as improved survival rates and LV function, compared with failed PCI 1, 4, 5, 6, 8, 15. In contrast, some observational studies suggest that successful CTO PCI is not associated with improvement of survival rates and cardiovascular events 16, 17.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate of percutaneous coronary intervention (PCI) for chronic total occlusion (CTO) lesions have been increased by the advancement of operator's skill, experience with intervention techniques (anterograde and retrograde approaches, wire manipulations techniques, and so on), and device technology (improved dedicated CTO guidewires, microcatheters, CTO balloons, and coronary stents) 1, 2, 3, 4. Several studies demonstrated that successful CTO intervention was associated with improved survival rates and angina symptom relief when compared with the failed CTO intervention 1, 4, 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-register data shows that successfully undergone CTO PCI improves patient prognosis (Mehran, 2011;Joyal, 2010). In our study, unfortunately, symptom evaluation of patients was not carried out, but, comparing survival after successful and unsuccessful CTO PCI, significantly better results were observed in the successful patient group (Fig.…”
Section: Discussionmentioning
confidence: 73%